Pengembangan program Adlerian group play counseling untuk meningkatkan daya tarik interpersonal siswa kelas V Sekolah Dasar - Ipah Saripah; Fajar Bilqis (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2019)
Research is motivated by the need for the development of the Adlerian Group Play Therapy program to increase interpersonal attractiveness. The research aims to develop the Adlerian Group Play Therapy program in increasing students' interpersonal attractiveness. The study was designed in the form of development research with a qualitative approach. Data analysis method in this research uses descriptive analysis. After receiving improvements from four expert lecturers & two homeroom teachers, this program can be used to increase the interpersonal attractiveness of elementary school students. The program consists of intervention subjects, intervention objectives, counselor competencies, implementation steps, success criteria, tools and media used, matrices, and Guidance and Counseling Service Activity Units